The Rainbow Scale for the Assessment of the Cervicomental Angle: A Validated Scale. (26th April 2019) - van de Lande, Lara S; Eyck, Ben M; Mooij, Jelle J; Stevens, Hieronymus P; van Dongen, Joris A
Abstract: Background: Aging of the neck results in an increased cervicomental angle, which can be treated by various surgical and nonsurgical procedures. To measure the success of these procedures, standardized validated objective photographic measurement tools are needed. However, no online standardized photographic measurement tools exist for the assessment of the cervicomental angle. Objectives: The purpose of this study was to establish a validated and reliable measurement tool for the assessment of the cervicomental angle based on the Rainbow Scale. Methods: A 5-point photographic rating scale was developed and created from 1 photograph with Adobe Photoshop. Fifteen reference photographs of women, 3 photographs per grade, were included for validation. Seven panelists (ie, plastic and maxillofacial surgeons) assessed the reference photographs 3 times with a minimal interval of 3 days in an online survey. Intra- and inter-observer agreements were calculated utilizing the weighted kappa coefficient. Results: Mean intra-observer agreement was 0.93 (0.78-1.00). Mean interobserver agreement was 0.796 (0.574-0.961) for survey 1, 0.868 (0.690-0.960) for survey 2, and 0.820 (0.676-0.959) for survey 3. Conclusions: The Rainbow Scale for the assessment of the cervicomental angle has been validated in an online fashion. The scale is reproducible and reliable and requires no learning curve. Potential applications include objective assessment of neck treatment planning and surgical outcome. Level of Evidence: 4: